Synthesis and functionalization of NaGdF4:Yb,Er@NaGdF4 core–shell nanoparticles for possible application as multimodal contrast agents - Baziulyte-Paulaviciene, Dovile; Karabanovas, Vitalijus; Stasys, Marius; Jarockyte, Greta; Poderys, Vilius; Sakirzanovas, Simas; Rotomskis, Ricardas (Beilstein Journal of Nanotechnology, 2017)
Upconverting nanoparticles (UCNPs) are promising, new imaging probes capable of serving as multimodal contrast agents. In this study, monodisperse and ultrasmall core and core–shell UCNPs were synthesized via a thermal decomposition method. Furthermore, it was shown that the epitaxial growth of a NaGdF4 optical inert layer covering the NaGdF4:Yb,Er core effectively minimizes surface quenching due to the spatial isolation of the core from the surroundings. The mean diameter of the synthesized core and core–shell nanoparticles was ≈8 and ≈16 nm, respectively. Hydrophobic UCNPs were converted into hydrophilic ones using a nonionic surfactant Tween 80. The successful coating of the UCNPs by Tween 80 has been confirmed by Fourier transform infrared (FTIR) spectroscopy. Scanning electron microscopy (SEM), powder X-ray diffraction (XRD), photoluminescence (PL) spectra and magnetic resonance (MR) T1 relaxation measurements were used to characterize the size, crystal structure, optical and magnetic properties of the core and core–shell nanoparticles. Moreover, Tween 80-coated core–shell nanoparticles presented enhanced optical and MR signal intensity, good colloidal stability, low cytotoxicity and nonspecific internalization into two different breast cancer cell lines, which indicates that these nanoparticles could be applied as an efficient, dual-modal contrast probe for in vivo bioimaging.
Keywords: cancer theranostics; core–shell structure; luminescence; multimodal; nanoparticles; upconverting nanoparticles; upconversion

(untitled) - Wang, M.; Abbineni, G.; Clevenger, A.; Mao, C.; Xu, S. (Nanomedicine: NBM, 2011)

(untitled) - Mader, H. S.; Kele, P.; Saleh, S. M.; Wolfbeis, O. S. (Curr. Opin. Chem. Biol., 2010)

(untitled) - Liu, C.; Gao, Z.; Zeng, J.; Hou, Y.; Fang, F.; Li, Y.; Qiao, R.; Shen, L.; Lei, H.; Yang, W.; Gao, M. (ACS Nano, 2013)

(untitled) - Deng, R.; Qin, F.; Chen, R.; Huang, W.; Hong, M.; Liu, X. (Nat. Nanotechnol., 2015)

(untitled) - Sun, Y.; Feng, W.; Yang, P.; Huang, C.; Li, F. (Chem. Soc. Rev., 2015)

(untitled) - Zhou, J.; Liu, Z.; Li, F. (Chem. Soc. Rev., 2012)

(untitled) - Wang, F.; Banerjee, D.; Liu, Y.; Chen, X.; Liu, X. (Analyst, 2010)

(untitled) - Wang, F.; Liu, X. (Chem. Soc. Rev., 2009)

(untitled) - Guanying, C.; Gang, H. (Theranostics, 2013)

(untitled) - Qiu, H.; Yang, C.; Shao, W.; Damasco, J.; Wang, X.; Ågren, H.; Prasad, P. N.; Chen, G. (Nanomaterials, 2014)

(untitled) - Liu, Y.; Tu, D.; Zhu, H.; Li, R.; Luo, W.; Chen, X. (Adv. Mater., 2010)

(untitled) - Wang, F.; Wang, J.; Liu, X. (Angew. Chem., 2010)

(untitled) - Chen, D.; Lei, L.; Yang, A.; Wang, Z.; Wang, Y. (Chem. Commun., 2012)

(untitled) - Liu, F.; He, X.; Liu, L.; You, H.; Zhang, H.; Wang, Z. (Biomaterials, 2013)

(untitled) - Cao, T.; Yang, T.; Gao, Y.; Yang, Y.; Hu, H.; Li, F. (Inorg. Chem. Commun., 2010)

(untitled) - Chen, Z.; Chen, H.; Hu, H.; Yu, M.; Li, F.; Zhang, Q.; Zhou, Z.; Yi, T.; Huang, C. (J. Am. Chem. Soc., 2008)

(untitled) - Bogdan, N.; Vetrone, F.; Ozin, G. A.; Capobianco, J. A. (Nano Lett., 2011)

(untitled) - Cheng, L.; Yang, K.; Zhang, S.; Shao, M.; Lee, S.; Liu, Z. (Nano Res., 2010)

(untitled) - Zhao, Y.; Wang, Z.; Zhang, W.; Jiang, X. (Nanoscale, 2010)

(untitled) - Huang, Y.; Zhang, B.; Xi, S.; Yang, B.; Xu, Q.; Tan, J. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Baalousha, M.; Arkill, K. P.; Romer, I.; Palmer, R. E.; Lead, J. R. (Sci. Total Environ., 2015)

(untitled) - Cascales, C.; Paíno, C. L.; Bazán, E.; Zaldo, C. (Nanotechnology, 2017)

(untitled) - Rogosnitzky, M.; Branch, S. (BioMetals, 2016)

(untitled) - Swaminathan, S. (Magn. Reson. Imaging, 2016)

(untitled) - Park, S.; Mohanty, N.; Suk, J. W.; Nagaraja, A.; An, J.; Piner, R. D.; Cai, W.; Dreyer, D. R.; Berry, V.; Ruoff, R. S. (Adv. Mater., 2010)

(untitled) - Yi, G.-S.; Chow, G.-M. (Chem. Mater., 2007)

(untitled) - Wong, H.-T.; Vetrone, F.; Naccache, R.; Chan, H. L. W.; Hao, J.; Capobianco, J. A. (J. Mater. Chem., 2011)

Book of abstracts of the “Chemistry and Chemical Technology - Baziulyte, D.; Karabanovas, V.; Stalnionis, M.; Jurciukonis, I.; Sakirzanovas, S. (International Conference of Lithuanian Society of Chemistry, 2016)

(untitled) - Johnson, N. J. J.; Oakden, W.; Stanisz, G. J.; Scott Prosser, R.; van Veggel, F. C. J. M. (Chem. Mater., 2011)

(untitled) - Hou, Y.; Qiao, R.; Fang, F.; Wang, X.; Dong, C.; Liu, K.; Liu, C.; Liu, Z.; Lei, H.; Wang, F.; Gao, M. (ACS Nano, 2013)

(untitled) - Vetrone, F.; Naccache, R.; de la Fuente, A. J.; Sanz-Rodriguez, F.; Blazquez-Castro, A.; Rodriguez, E. M.; Jaque, D.; Solé, J. G.; Capobianco, J. A. (Nanoscale, 2010)

(untitled) - Karabanovas, V.; Zitkus, Z.; Kuciauskas, D.; Rotomskis, R.; Valius, M. (J. Biomed. Nanotechnol., 2014)

(untitled) - Osman, O.; Zanini, L. F.; Frénéa-Robin, M.; Dumas-Bouchiat, F.; Dempsey, N. M.; Reyne, G.; Buret, F.; Haddour, N. (Biomed. Microdevices, 2012)

(untitled) - Wang, S.-H.; Lee, C.-W.; Chiou, A.; Wei, P.-K. (J. Nanobiotechnol., 2010)

(untitled) - Woźniak, A.; Noculak, A.; Gapiński, J.; Kociolek, D.; Boś-Liedke, A.; Zalewski, T.; Grześkowiak, B. F.; Kołodziejczak, A.; Jurga, S.; Banski, M.; Misiewicz, J.; Podhorodecki, A. (RSC Adv., 2016)

(untitled) - Guller, A. E.; Generalova, A. N.; Petersen, E. V.; Nechaev, A. V.; Trusova, I. A.; Landyshev, N. N.; Nadort, A.; Grebenik, E. A.; Deyev, S. M.; Shekhter, A. B.; Zvyagin, A. V. (Nano Res., 2015)

(untitled) - Ren, W.; Tian, G.; Jian, S.; Gu, Z.; Zhou, L.; Yan, L.; Jin, S.; Yin, W.; Zhao, Y. (RSC Adv., 2012)